The role of STEM-based learning media in improving students' science literacy: A systematic review - Siahaan, Sardianto Markos; Tina Oktasari; Leni Marlina (Universitas Negeri Yogyakarta, 2025)
In the 21st century, scientific literacy is an essential skill for students, but many challenges remain in learning it. To address these challenges, integrating STEM-based learning media offers an innovative solution by promoting contextual, interactive, and project-based learning that enhances students’ engagement, critical thinking, and understanding of scientific concepts. This study aims to systematically review the role of STEM-based learning media in improving students' science literacy, identify the characteristics of effective media, and the factors that influence their successful implementation. This study used a systematic review method following PRISMA guidelines, analysing 21 selected articles from Google Scholar, Web of Science, DOAJ, and ERIC databases, with a publication range of 2019-2025. The analysis shows that STEM-based media effectively improve students' understanding of science concepts, critical thinking skills, and digital literacy. Interactive, project-based and contextualised media proved most effective. The main supporting factors for successful implementation include teacher competence, valid and practical media design, and support for the learning environment. This study emphasises the importance of integrating STEM-based learning media to improve overall science literacy. Future research is recommended to explore the long-term impact of STEM-based learning media on students' science literacy across diverse educational levels and cultural contexts, and to develop adaptive digital tools that support personalised learning and teacher facilitation.